2020
DOI: 10.1001/jamanetworkopen.2020.24577
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adverse Neighborhood Exposures With HIV Viral Load in Pregnant Women at Delivery

Abstract: IMPORTANCE Racial disparities in maternal morbidity and mortality are in large part driven by poor control of chronic diseases. The association between adverse neighborhood exposures and HIV virologic control has not been well described for women with HIV during pregnancy. OBJECTIVE To evaluate the association between adverse neighborhood exposures and HIV viral load at delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This construct focuses on the range of economic and social resources of a neighborhood’s residents. Among the 23 studies that discussed neighborhood level SES, two studies discussed its outcomes on ART initiation [ 67 , 79 ], two studies discussed ART adherence [ 81 , 86 ], 15 studies discussed HIV viral suppression[ 70 , 72 , 77 , 78 , 80 82 , 88 , 91 , 93 95 , 99 , 100 ], and 6 studies combined neighborhood SES factors into a composite measure, making it difficult to assess the impact of each factor individually [ 68 , 74 , 75 , 85 , 87 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This construct focuses on the range of economic and social resources of a neighborhood’s residents. Among the 23 studies that discussed neighborhood level SES, two studies discussed its outcomes on ART initiation [ 67 , 79 ], two studies discussed ART adherence [ 81 , 86 ], 15 studies discussed HIV viral suppression[ 70 , 72 , 77 , 78 , 80 82 , 88 , 91 , 93 95 , 99 , 100 ], and 6 studies combined neighborhood SES factors into a composite measure, making it difficult to assess the impact of each factor individually [ 68 , 74 , 75 , 85 , 87 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of the fifteen studies assessing HIV viral suppression, seven found no association with neighborhood level income [ 70 , 72 , 78 ], affluence [ 80 ], residential stability [ 80 , 81 ], health care access [ 70 , 80 ], and food accessibility [ 88 , 99 ]. Six studies found inverse associations with HIV viral suppression and neighborhood level income [ 95 ], education [ 81 , 82 , 100 ], lack of car ownership [ 77 , 81 , 100 ], residential instability [ 91 ], percent of female-headed households [ 81 ], and food inaccessibility [ 80 ]. A positive association with HIV viral suppression was observed among men who have sex with men (MSM) living in areas that were more concentrated with MSM-headed households [ 70 ], neighborhoods with low poverty, low unemployment, high insurance coverage, and high education attainment [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of epidemiological and health research indicates that broader neighborhood factorssuch as objective measures of poverty or residential stabilityare associated with physical and mental health problems. [13][14][15] Fewer studies have looked at the associations between stress related to neighborhood crimesuch as violent crime rates as reported by law enforcement agenciesand increased health problems, however growing research suggests a positive association between living in neighborhoods with higher crime and experiencing more mental health problems, including stress, anxiety, and depression. [16][17][18][19] Fewer still have examined this association intergenerationally to assess whether these risks are transmitted to offspring in a manner that impacts their wellbeing, 7 and to our knowledge none have looked beyond birth outcomes.…”
Section: Introductionmentioning
confidence: 99%